1971
DOI: 10.1126/science.173.4002.1103
|View full text |Cite
|
Sign up to set email alerts
|

Physiological Role of Pleasure

Abstract: A given stimulus can induce a pleasant or unpleasant sensation depending on the subject's internal state. The word alliesthesia is proposed to describe this phenomenon. It is, in itself, an adequate motivation for behavior such as food intake or thermoregulation. Therefore, negative regulatory feedback systems, based upon oropharingeal or cutaneous thermal signals are peripheral only in appearance, since the motivational component of the sensation is of internal origin. The internal signals seem to be complex … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

27
573
0
9

Year Published

1981
1981
2000
2000

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 1,355 publications
(609 citation statements)
references
References 14 publications
27
573
0
9
Order By: Relevance
“…It is worthwhile to consider some of the possible mechanisms through which such specific satieties might act. Cabanac and his colleagues suggested that the change they observed in the pleasantness of sucrose solutions or food-related odors after a preload of glucose was due to changes in the internal state or need for particular nutrients [3,8]. The decrease in pleasantness was found only if the substance ingested was similar to that tasted, i.e.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…It is worthwhile to consider some of the possible mechanisms through which such specific satieties might act. Cabanac and his colleagues suggested that the change they observed in the pleasantness of sucrose solutions or food-related odors after a preload of glucose was due to changes in the internal state or need for particular nutrients [3,8]. The decrease in pleasantness was found only if the substance ingested was similar to that tasted, i.e.…”
Section: Discussionmentioning
confidence: 99%
“…This led to the present investigation of satiety and its specificity in man. In relation to satiety in man it has been shown that the pleasantness of the taste or smell of food-related test stimuli was decreased by a 50 g load of glucose which was either swallowed or delivered intragastrically [3,4,6,7]. Cabanac and his colleagues I6,8] showed that the glucose load decreased the pleasantness of sucrose solutions but not of salt solutions, and that eating a meal decreased the pleasantness of food-related odors but not of non-food-related odors.…”
Section: Specificity Of Satietymentioning
confidence: 99%
See 2 more Smart Citations
“…The findings strongly support this interpretation of earlier, behaviourally less conclusive data. Thus, the volume of a meal is not determined just by the decrease in all palatability as deprivation arousal declines (Booth, 1972a;Cabanac, 1971) and the decrease in the palatability specifically of the food just eaten (e.g. Berridge, 1991;Booth, 1976;Clifton et al, 1987;Rolls et al, 1983).…”
Section: Discussionmentioning
confidence: 99%